2011
DOI: 10.1210/jc.2011-1073
|View full text |Cite
|
Sign up to set email alerts
|

Is the Incidence of Congenital Hypothyroidism Really Increasing? A 20-Year Retrospective Population-Based Study in Québec

Abstract: Estimating the incidence of CH is influenced by minimal changes in TSH screening cutoffs. Lower cutoffs identify additional cases that have predominantly functional disorders whose impact on intellectual disability, if left untreated, remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
169
3
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(202 citation statements)
references
References 40 publications
10
169
3
20
Order By: Relevance
“…It is reported to have an incidence of 1 in 5,727 and it is more common in females. 1 The majority of these patients are asymptomatic; however, some may have obstructive symptoms. 2,3 Hypothyroidism was present in 62% of patients with lingual thyroid in one series, 4 while hyperthyroidism is rare.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported to have an incidence of 1 in 5,727 and it is more common in females. 1 The majority of these patients are asymptomatic; however, some may have obstructive symptoms. 2,3 Hypothyroidism was present in 62% of patients with lingual thyroid in one series, 4 while hyperthyroidism is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Two thirds of the cases are due to thyroid dysgenesis (thyroid ectopy, athyreosis and thyroid hypoplasia) with a prevalence of 1 in 4,000 newborn infants, which has remained stable over the last 20 years in our jurisdiction 17 and which is not influenced by seasonal factors 5 . Ten to fifteen percent are due to recessively inherited defects in hormone synthesis resulting in goiter (birth prevalence of 1:30,000), while a growing number of cases, as a consequence of lower TSH cut-offs, are due to mild functional disorders with a normal thyroid gland in situ (15-20%, birth prevalence of 1:20,000 to 1:15,000) 17 .…”
Section: Basicsmentioning
confidence: 89%
“…Permanent primary congenital hypothyroidism is the most common form of congenital hypothyroidism, and is in fact the most common congenital endocrine disorder: estimates of its prevalence depend on the screening methods, algorithms and cut-offs used but average 1 in 2,500 newborn infants [16][17][18] . Two thirds of the cases are due to thyroid dysgenesis (thyroid ectopy, athyreosis and thyroid hypoplasia) with a prevalence of 1 in 4,000 newborn infants, which has remained stable over the last 20 years in our jurisdiction 17 and which is not influenced by seasonal factors 5 .…”
Section: Basicsmentioning
confidence: 99%
“…Corbetta et al reported a higher rate of newborns with a normally located thyroid gland which represents two-thirds of the overall CH population [7]. In Canada, Deladoey et al found that lowering the cutoff point resulted in identifying more mild CH forms with a normally located thyroid gland [28].…”
Section: Discussionmentioning
confidence: 99%